2017
DOI: 10.1080/10584609.2016.1267053
|View full text |Cite
|
Sign up to set email alerts
|

Voting Advice Applications and Electoral Participation: A Multi-Method Study

Abstract: Voting Advice Applications (VAAs) help users casting a vote by offering an explicit ranking of viable options. The wide amount of readily available information provided by VAAs to users has been shown to contribute to reducing the transactional costs involved in gathering relevant political information. Available evidence also supports the idea that VAA users are more likely to cast a ballot in elections as a result. The extent to which electoral participation is caused by using a VAA, however, remains unclear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…While these debates largely relate to who is using the technology, Gibson and McAllister (2015) also specifically relate them to who benefits from the technology, providing evidence that green parties appeared to benefit more from using social media than their more mainstream competitors in Australian elections, a finding they relate to the fact that these voters are typically drawn from younger demographics (see Gibson & McAllister, 2015, p.542). Recent studies showing that social media have a positive impact on the youth vote seem to support this idea (Vaccari, 2017;Garzia, Trechsel, & De Angelis 2017;Aldrich, Gibson, Cantijoch & Konitzer, 2015). 2 Hence, we develop our next hypothesis: H3: Politicians from smaller parties will benefit more from campaigning on Twitter…”
Section: Political Campaigning On Twitter: Mechanisms and Moderators mentioning
confidence: 98%
“…While these debates largely relate to who is using the technology, Gibson and McAllister (2015) also specifically relate them to who benefits from the technology, providing evidence that green parties appeared to benefit more from using social media than their more mainstream competitors in Australian elections, a finding they relate to the fact that these voters are typically drawn from younger demographics (see Gibson & McAllister, 2015, p.542). Recent studies showing that social media have a positive impact on the youth vote seem to support this idea (Vaccari, 2017;Garzia, Trechsel, & De Angelis 2017;Aldrich, Gibson, Cantijoch & Konitzer, 2015). 2 Hence, we develop our next hypothesis: H3: Politicians from smaller parties will benefit more from campaigning on Twitter…”
Section: Political Campaigning On Twitter: Mechanisms and Moderators mentioning
confidence: 98%
“…Accordingly, results from the existing research on VAA effects on participation are relatively straightforward: VAA usage would seem to be systematically linked to an increased propensity to take part in elections, regardless of the methodology employed by the various available studies. In this respect, the findings stemming from early analyses of opt-in surveys of VAA users (Fivaz & Nadig, 2010;Ladner & Pianzola, 2010;Marschall, 2005;Marschall & Schmidt, 2010) are corroborated by statistical analyses of representative survey data sets Garzia, De Angelis, & Pianzola, 2014;Gemenis & Rosema, 2014;Marschall & Schultze, 2012;Pianzola, 2014) and experimental designs (Enyedi, 2015;Garzia, Trechsel, & De Angelis, 2016;Vassil, 2012).…”
Section: Vaas and Their Effectsmentioning
confidence: 92%
“…This type of research has shown that design choices can have a great impact on the advice that the tools generate, and that the use of spatial models leads to high demands on the data used for constructing the models that underlie the advice. Other studies have focused on the consequences of VAA usage, such as effects on political knowledge (Schultze, ), political interest (Kruikemeier, van Noort, Vliegenthart, & de Vreese, ), electoral turnout (Dinas, Trechsel, & Vassil, ; Garzia, De Angelis, & Pianzola, ; Gemenis & Rosema, ), electoral volatility (Ladner, Fivaz, & Pianzola, ), and party choice (Walgrave, Van Aelst, & Nuytemans, ; Wall, Krouwel, & Vitiello, ). Although the results are mixed, on the basis of these studies we can safely state that VAAs have an impact on voters’ behavior, both in terms of electoral turnout and in terms of party choice.…”
Section: Introductionmentioning
confidence: 99%